Assessment of communication of socially responsible activities in selected companies - Stříteská, Michaela; Bartáková, Kateřina (Univerzita Pardubice, 2012)
Significance of socially responsible business activities has been growing constantly in recent years, mainly in the context of increasing competitiveness and gaining of goodwill. The companies pay bigger and bigger attention to the area of social responsibility and spend more and more financial funds on it. However, the specialists in theory and practice agree that companies do not know how to communicate these activities efficiently. And communication of CSR activities towards stakeholders is one of the key steps of successful introduction and efficient development of corporate social responsibility. Therefore the main aim of this paper is to analyse and assess how socially responsible companies fulfil and communicate their CSR activities towards their stakeholders. In this respect, responsible companies are considered to be the entities which were acknowledged as regards application of social responsibility. A basic precondition is the fact that these companies are active in the area of social responsibility, they communicate their responsibility towards their stakeholders in a certain way and they try to publish their CSR activities.
Keywords: corporate social responsibility; responsible behaviour; communication; reporting; triple bottom line; stakeholder